Atypical Central Retinal Artery Occlusion following COVID-19 Infection: A Case Report - Hamid Reza Heidarzadeh; Mojtaba Abrishami; Mehrdad Motamed Shariati; Seyed Hossein Ghavami Shahri; Mohammad Reza Ansari Astaneh (Case Reports in Ophthalmology, 2023)
Herein, we report a patient with atypical central retinal artery occlusion (CRAO) following COVID-19 recovery. A 44-year-old male was referred to the emergency room with a history of diplopia and sudden-onset painless visual loss in his left eye. He had a history of 1-week hospitalization for severe COVID-19 infection with pneumonia 3 weeks before, with positive real-time reverse transcription polymerase chain reaction result for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in a nasopharyngeal sample. His visual acuity in the left eye was light perception which became no light perception later. Relative afferent pupillary defect was positive in the left eye. He had anterior chamber and anterior vitreous cells due to spillover and white cotton-wool-like patches in the left eye. He was diagnosed with atypical CRAO with uveitis-like features. After 3 weeks, he developed neovascular glaucoma and was treated with panretinal photocoagulation. In conclusion, SARS-CoV-2-induced vasculopathy and hypercoagulopathy conditions may be involved in the progression of CRAO in our patient. COVID-19 could be a considerable predisposing factor for CRAO.